Bronchial allergen provocation: A useful method to assess the efficacy of specific immunotherapy in children. Issue 5 (11th April 2013) - Rosewich, Martin; Arendt, Sonja; El Moussaoui, Samir; Schulze, Johannes; Schubert, Ralf; Zielen, Stefan
Abstract: Background: The clinical efficacy of subcutaneous allergen‐specific immunotherapy (SCIT) varies between patients. New preparations are under development, and an objective tool with which to evaluate their efficacies in individual patients has become necessary. Our primary research question is whether bronchial allergen provocation (BAP) can be used to assess the efficacy of SCIT. Methods: In 42 house dust mite (HDM) allergic children (average age: 8.6 yr) with asthma, we analysed the clinical and objective improvements of a standardised HDM allergoid. All patients underwent two BAPs, one before SCIT and another 1 yr after SCIT. Fourteen patients who were recommended but chose not to undergo SCIT represented the control group. The total and specific IgE were analysed before SCIT; in addition, after SCIT, specific IgG and IgG4 were analysed. Results: After SCIT, the patients' allergen‐specific bronchial hyper‐reactivity (BHR) was significantly improved; specifically, their PD20 FEV1 was 34.4 AU before and 63.3 AU after SCIT (p < 0.01). The PD20 FEV1 of the control group remained unchanged. Although BHR improved significantly in the treatment group, we were able to differentiate between the responders (n = 17, 60.7%) and non‐responders (n = 11, no improvement in BAP). The patients in both groups stated that SCIT had led to a subjective improvement in their symptoms, in contrast to the untreated control group, but only the responders required less medication after SCIT (p < 0.01). Conclusions: After 1 yr of SCIT against HDM, 60.7% of the patients observed in this study exhibited significant improvements, as defined by BAP. However, BAP was also able to identify the non‐responders to treatment. Thus, BAP is a useful and objective method of estimating the effectiveness of SCIT and is not influenced by a placebo effect. Abstract :